2018
DOI: 10.5539/jas.v10n8p56
|View full text |Cite
|
Sign up to set email alerts
|

The cDNA Structures and Expression Profile of the Ascorbate Peroxidase Gene Family During Drought Stress in Wild Watermelon

Abstract: Ascorbate peroxidase (APX) plays an important role in detoxifying reactive oxygen species under environmental stress. Although previous work in drought-tolerant wild watermelon has shown an increase in chloroplast APX enzyme activity under drought, molecular entities of APX have remained uncharacterized. In this study, structure and transcriptional regulation of the APX gene family in watermelon were characterized. Five APX genes, designated as CLAPX1 to CLAPX5, were identified from watermelon genome. The mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Recent studies show that the cis-elements in APX genes contribute to the plant abiotic and phytohormones stress responses. Similar types of abiotic and phytohormone-related cis-regulatory elements have been identified in previous studies (Akbudak et al, 2018;Malambane et al, 2018;Tao et al, 2018;Liao et al, 2020;Tyagi et al, 2020;Wang et al, 2022). Furthermore, AhAPXs gene functions were further predicted by GO enrichment analysis (Figure 10), which also supported the role of these genes in ROS scavenging and stress response mechanisms.…”
Section: The Contribution Of Apx Genes Toward Stress Responses and To...supporting
confidence: 83%
See 3 more Smart Citations
“…Recent studies show that the cis-elements in APX genes contribute to the plant abiotic and phytohormones stress responses. Similar types of abiotic and phytohormone-related cis-regulatory elements have been identified in previous studies (Akbudak et al, 2018;Malambane et al, 2018;Tao et al, 2018;Liao et al, 2020;Tyagi et al, 2020;Wang et al, 2022). Furthermore, AhAPXs gene functions were further predicted by GO enrichment analysis (Figure 10), which also supported the role of these genes in ROS scavenging and stress response mechanisms.…”
Section: The Contribution Of Apx Genes Toward Stress Responses and To...supporting
confidence: 83%
“…Previous studies showed that APX family genes are usually clustered into four major groups based on their subcellular localization or tree topologies (Pandey et al, 2011;Malambane et al, 2018;Tyagi et al, 2020). In the present study, all APX genes from four plant species were grouped into 11 main groups based on tree topologies and sequence similarities (Figure 2).…”
Section: Characterization and Evolution Of Apx Gene Family In Plantsmentioning
confidence: 52%
See 2 more Smart Citations
“…In this study, two genes encoding APX were up-regulated and four were down-regulated. Similarly, in the study of Citrullus lanatus, the changes of APX genes are different under drought stress (Goitseone et al, 2018). The post-harvest petals of cut rose (Rosa hybrida cv.…”
Section: Signaling Pathway Mediates Drought-stress Responsesmentioning
confidence: 99%